1996
DOI: 10.1002/lt.500020405
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in patients with posttransplant diabetes mellitus following orthotopic liver transplantation

Abstract: It is not well understood whether posttransplant diabetes mellitus (PTDM) following orthotopic liver transplantation (OLTx) alters postoperative morbidity. This study was designed to evaluate this question. All adult patients who received an OLTx between July 1985 and March 1993 (n = 497) were evaluated by retrospective chart review for evidence of PTDM after OLTx. The patients identified with PTDM (n = 26) were case matched with nondiabetic OLTx recipients based on primary liver disease diagnosis, age, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 15 publications
2
55
0
1
Order By: Relevance
“…18,19 When de novo posttransplant insulin-dependent diabetes is strictly defined as diabetes presenting beyond the first postoperative month but within 30 days of discharge, the prevalence is 5.2%, but a need for long-term insulin therapy does not necessarily ensue. 20 In fact, when patients who develop de novo posttransplant diabetes are followed for 3 years, the prevalence of insulin use falls progressively from 26% at 1 year, to 9% at 2 years, and to 1% at 3 years. 17 Posttransplant diabetes is more likely in patients with pretransplant diabetes (than in nondiabetics), in those with high pretransplant blood sugar levels, 18,20 and in those who have many episodes of steroid-resistant rejection.…”
Section: Prevalence Of Diabetes In Liver Transplant Recipientsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 When de novo posttransplant insulin-dependent diabetes is strictly defined as diabetes presenting beyond the first postoperative month but within 30 days of discharge, the prevalence is 5.2%, but a need for long-term insulin therapy does not necessarily ensue. 20 In fact, when patients who develop de novo posttransplant diabetes are followed for 3 years, the prevalence of insulin use falls progressively from 26% at 1 year, to 9% at 2 years, and to 1% at 3 years. 17 Posttransplant diabetes is more likely in patients with pretransplant diabetes (than in nondiabetics), in those with high pretransplant blood sugar levels, 18,20 and in those who have many episodes of steroid-resistant rejection.…”
Section: Prevalence Of Diabetes In Liver Transplant Recipientsmentioning
confidence: 99%
“…20 In fact, when patients who develop de novo posttransplant diabetes are followed for 3 years, the prevalence of insulin use falls progressively from 26% at 1 year, to 9% at 2 years, and to 1% at 3 years. 17 Posttransplant diabetes is more likely in patients with pretransplant diabetes (than in nondiabetics), in those with high pretransplant blood sugar levels, 18,20 and in those who have many episodes of steroid-resistant rejection. 20 The results of at least three studies have suggested that diabetes is more likely to occur in patients who receive a liver transplantation for hepatitis C than other diagnoses.…”
Section: Prevalence Of Diabetes In Liver Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of universal agreement, some studies have observed worsened short-and mid-term survival among diabetic LT recipients. [1][2][3][4][5][6][7] Furthermore, DM is a wellknown risk factor for cardiovascular disease, which is one of the leading causes of death of LT recipients in the long term. 8 Calcineurin inhibitors (CI) also predispose to DM through islet cell toxicity, diminished insulin synthesis or release, as well as decreased peripheral insulin sensitivity.…”
Section: D Abetes Mellitus (Dm)mentioning
confidence: 99%
“…High blood glucose levels that may be observed for various reasons during liver transplant may negatively affect postoperative morbidity and mortality. 6 Many treatments such as immunosuppressive drugs used after liver transplant, blood and blood product replacements, mechanical ventilation, invasive procedures for diagnosis and treatment, and catheterizations are risk factors for various infections. 7 In this study, we aimed to determine the effects of intraoperative hyperglycemia on postoperative outcomes in orthotopic liver transplant recipients.…”
Section: Introductionmentioning
confidence: 99%